2018
DOI: 10.1186/s12879-018-3291-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of helminthic infections and determinant factors among pregnant women in Mecha district, Northwest Ethiopia: a cross sectional study

Abstract: BackgroundIntestinal parasites are the most common infections in developing countries. Prevalence and impacts of these parasites are high in pregnant women. The aims of this study were to determine prevalence of helminthic infection and evaluate the determinant factors during pregnancy.MethodsA cross-sectional study was conducted in Mecha district from November 2015 to January 2016. The data were collected by interview technique and collecting the stool sample from each pregnant woman. Descriptive statistics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 24 publications
11
61
6
2
Order By: Relevance
“…This finding was in line with 2018 finding from Ethiopia [42]. This is because regular hand washing practice breaks the life cycles of intestinal parasitic infection from an infected host to susceptible host [43].…”
Section: Resultssupporting
confidence: 91%
“…This finding was in line with 2018 finding from Ethiopia [42]. This is because regular hand washing practice breaks the life cycles of intestinal parasitic infection from an infected host to susceptible host [43].…”
Section: Resultssupporting
confidence: 91%
“…Regular handwashing practice decreases the odds of intestinal parasitic infection by 60%. This finding was in line with 2018 finding from Ethiopia [37]. This is because the feco-oral route of transmission will be blocked by applying regular handwashing practice [38].…”
Section: Intestinal Parasitic Infection Among Childrensupporting
confidence: 89%
“…Other studies in Ethiopia reported assorted magnitudes and patterns, suggesting the existence of substantial variation in the epidemiology of intestinal parasites in the country [13,20,[28][29][30]. A study in Mecha district, Northwest Ethiopia reported an exceptionally high prevalence (70%) and identified A. lumbricoides (33%), S. mansoni (17%) and Hookworms (14%) as the predominant infections [29]. A study among pregnant women following ANC in a referral hospital in Northwest Ethiopia reported a comparable figure to our finding (32%) yet the major infections were protozoan: G. lamblia (13%) and E. histolytica (8%) [30].…”
Section: Discussionmentioning
confidence: 97%
“…In this study the overall magnitude of the intestinal parasitic infection was 39%, with the highest prevalence for A. lumbricoides (25%) and hookworms (11%). Other studies in Ethiopia reported assorted magnitudes and patterns, suggesting the existence of substantial variation in the epidemiology of intestinal parasites in the country [13,20,[28][29][30]. A study in Mecha district, Northwest Ethiopia reported an exceptionally high prevalence (70%) and identified A. lumbricoides (33%), S. mansoni (17%) and Hookworms (14%) as the predominant infections [29].…”
Section: Discussionmentioning
confidence: 98%